A 3D-printed lightweight broadband electromagnetic absorbing metastructure with preserved high-temperature mechanical property. (15th October 2021) - Yang, Zhen; Liang, Qingxuan; Duan, Yubing; Li, Zhaohui; Li, Dichen; Cao, Yi
Highlights: The metastructure with the compass-like ITO resonator realized broadband absorbing. The perforated designing for dielectric layer improved the working bandwidth. The designed perforated PEEK substrate decreased the structure's density obviously. The 3D-printed PEEK substrate showed good high-temperature compression strength. Abstract: light-weight metastructures that possess excellent electromagnetic(EM) absorbing performance and high-temperature mechanical property for real-life applications are highly desirable, but not yet realized to date. Herein, a novel metastructure, which enables to achieve both excellent EM absorbing ability and preeminent mechanical property, was proposed and realized experimentally. Benefiting from the flexibility of Fused Deposition Modeling (FDM) technique, the EM metastructure was fabricated with a distinct perforated Poly-Ether-Ether-Ketone (PEEK) dielectric substrate attaching Indium Tin Oxide (ITO) resonator. The perforated PEEK substrate realized not only being lightweight but also increasing the EM absorbing bandwidth. Moreover, owing to extraordinary mechanical, thermal and physical performance of PEEK material, the proposed metastructure also demonstrated good compression strength in high temperature range. This work opens a new avenue to promote the practical application of EM absorbing metastructure.